A efetividade da atuação do Tribunal de Contas do Estado do Rio de Janeiro na sustação de ato e/ou contrato: a perspectiva dos stakeholders - Alves, Cláudio Benedito da Fonseca (2009)
The object of this dissertation is to identify the perception of stakeholders related to the organizational action taken by the Account Court of Rio de Janeiro State TCERJ in the use of one of his institutional responsibilities, interruption of the implementation of act and/or contract, plus case study. Identifying, from the contribution of stakeholders, possible deficiencies and potential fixes in the performance of the state agency in exercising jurisdiction in focus.